Atrial fibrillation surgery with a focus on patients with reduced left ventricular function and heart failure. Issue 4 (14th February 2020) - Petersen, Johannes; Reichenspurner, Hermann; Pecha, Simon
Abstract: This review article aims to give an overview on the different surgical treatment options for atrial fibrillation It includes concomitant- as well as stand-alone surgical ablation therapy and outlines the main issues in patients with heart failure and reduced LVEF.